A closed-handed affair: positive-strand RNA virus polymerases. (August 2014) - Subissi, Lorenzo; Decroly, Etienne; Selisko, Barbara; Canard, Bruno; Imbert, Isabelle
ABSTRACT : RNA viruses are important emerging pathogens that cause human and animal infectious diseases. Antiviral therapies have to deal with the high mutational capacity of RNA viruses, which quickly adapt to new environments. A primary target for antiviral drug development is the viral RNA-dependent RNA polymerase (RdRp), which is the central enzyme of the viral RNA replication/transcription machinery. Here, we review the current mechanistic and structural knowledge on RdRps of positive-strand RNA viruses gained through crystallography and biochemistry. In addition, we review the growing body of information on RdRp-mediated strategies, such as proofreading and genome end repair, used by positive-strand RNA viruses to maintain their genome integrity.